Sustaining Economic Welfare : Estimating Changes in Per Capita Wealth - Hamilton, Kirk (World Bank, Washington, DC, 2014)
The World Bank's "World Development Indicators 1999" highlights for the first time the "genuine" rate of saving for more than 100 countries around the globe. Genuine saving values the total change in economic assets, thereby providing an indicator of whether an economy is on a sustainable path. The Bank's new estimates of genuine saving broaden the usual national accounts definitions of assets to include human capital, minerals, energy, forest resources, and the stock of atmospheric carbon dioxide. Genuine saving measures the change in total assets rather than the change in per capita assets. Genuine saving data may answer the question, "Did total wealth rise or fall over the acoounting period?" But they do not address the question of whether an economy is sustainable with a growing population. Genuine saving could be positive even though per capita wealth is declining. The author explores the issue of measuring changes in per capita wealth--factoring in both growth in total assets (as measured by genuine saving) and population growth--as a more comprehensive indicator of sustainability. First he develops a theoretical approach to estimating total wealth. Then he presents cross-country estimates of changes in per capita wealth. Based on preliminary estimates, he concludes that in the majority of countries below the median per capita income, wealth is accumulating more slowly than the population is growing.